Influence of Ionospheric Scintillation on GNSS Satellite Constellation Geometry - Zauli, Felipe; Moraes, Alison de O.; Oliveira, Cesar B. A. de; Vani, Bruno C.; Santos, Jonas Sousa; Perrella, Waldecir J.; Monico, Joao F. G. [UNESP]; IEEE (Ieee, 2018)
Ionospheric scintillation is a serious concern for GPS users under low latitude regions. Under extreme cases, scintillation may lead to a full disruption of the receiver operation. This work presents a statistical analysis of ionospheric scintillation data measured by receivers belonging to CIGALA/CALIBRA network throughout Brazil. The main objective is to investigate how ionospheric irregularities may affect the GPS satellites available in the sky and consequently impact on positioning accuracy. The results show that a user near the crest of the equatorial ionization anomaly will be susceptible to such phenomenon and users in this region can be seriously harmed.
Keywords: GNSS; Ionosphere; Scintillation